Congestive nephropathy: a neglected entity? Proposal for diagnostic criteria and future perspectives. (30th November 2020) - Husain‐Syed, Faeq; Gröne, Hermann‐Josef; Assmus, Birgit; Bauer, Pascal; Gall, Henning; Seeger, Werner; Ghofrani, Ardeschir; Ronco, Claudio; Birk, Horst‐Walter
Abstract: Venous congestion has emerged as an important cause of renal dysfunction in patients with cardiorenal syndrome. However, only limited progress has been made in differentiating this haemodynamic phenotype of renal dysfunction, because of a significant overlap with pre‐existing renal impairment due to long‐term hypertension, diabetes, and renovascular disease. We propose congestive nephropathy (CN) as this neglected clinical entity. CN is a potentially reversible subtype of renal dysfunction associated with declining renal venous outflow and progressively increasing renal interstitial pressure. Venous congestion may lead to a vicious cycle of hormonal activation, increased intra‐abdominal pressure, excessive renal tubular sodium reabsorption, and volume overload, leading to further right ventricular (RV) stress. Ultimately, renal replacement therapy may be required to relieve diuretic‐resistant congestion. Effective decongestion could preserve or improve renal function. Congestive acute kidney injury may not be associated with cellular damage, and complete renal function restoration may be a confirmatory diagnostic criterion. In contrast, a persistently low renal perfusion pressure might induce renal dysfunction and histopathological lesions with time. Thus, urinary markers may differ. CN is mostly seen in biventricular heart failure but may also occur secondary to pulmonary arterial hypertension and elevated intra‐abdominal pressure. An increase in central venous pressure to >6 mmHg is associated with a steep decrease in glomerular filtration rate. However, the central venous pressure range that can provide an optimal balance of RV and renal function remains to be determined. We propose criteria to identify cardiorenal syndrome subgroups likely to benefit from decongestive or pulmonary hypertension‐specific therapies and suggest areas for future research.